Ionic conductivity of polyvinyl alcohol-based gel electrolyte containing diethyl carbonate plasticizer for supercapacitor application - Mohd Abid, Mohd Asyadi Azam; Abdul Aziz, Mohd Fareezuan; Tunku Adaham, Tunku Aidil Ilham; Tan, Jun Yu; Takasaki, Akito (Penerbit UTM Press, 2022)
In this study, diethyl carbonate (DEC) as a plasticizer have been added to the gel electrolytes (GEs) system to influence the conductivity and storage performance of supercapacitor. The GE was prepared through a stirring method consisting of ethylene carbonate (EC), propylene carbonate (PC), potassium iodide (KI), polyvinyl alcohol (PVA) and dimethyl sulfoxide (DMSO). Consecutively, 5 wt. % DEC as a plasticizer was added for all samples. The GE preparation started with stirring all materials and heated until a homogenous gel was formed. The prepared GEs have been characterized with electrochemical impedance spectroscopy (EIS), which utilized to study the ionic conductivity of them. Sample with 15 wt. % of DEC in GE has the ionic conductivity of ~6 x 10-3 Scm-1. This study shows that by adding DEC will cause the ionic conductivity improved which is suggested that this DEC enhanced the ion’s mobility in the GEs’ structures. In cyclic voltammetry, the gel electrolyte with 15 wt.% DEC attain the highest specific capacitance of 55.56 Fg-1 (scan rate of 10 mV s-1). The charge-discharge curve of gel electrolyte acquires a shark fin-like shape which is alike with an ideal supercapacitor symmetric triangle shape. To summarize, the development of high conductivity GE may provide the path for high-performance supercapacitor.